Primary mediastinal hydatid disease leading to popliteal artery hydatid cyst embolization - Hakeem, Aijaz (Medknow Publications, 2009)
Hydatid disease is a zoonosis caused by Echinococcus granulosus. Infected dogs release eggs through their feces and the eggs infect humans through food and water. The most common locations of hydatid cysts are the liver and lungs, but primary mediastinal involvement, though rare, can be encountered. We report on a 16-year-old female with a primary mediastinal hydatid cyst leading to popliteal arterial embolization. The mediastinal lesion was treated with partial pericystectomy with removal of the germinal membrane and prophylactic albendazole. In endemic areas, it is important to consider hydatid cysts in the differential diagnosis of an acute arterial occlusion.